한국인 역류 식도염 환자의 식도 상피 세포 사이 간격 확장과 Esomeprazole 투여 후의 변화 - 김재환; Jae Hwan Kim; 지삼룡; Sam Ryong Jee; 박성재; Sung Jae Park; 양성연; Sung Yeun Yang; 박은택; Eun Taik Park; 이연재; Youn Jae Lee; et al. (Journal of neurogastroenterology and motility, 2006)
목적: 서구에서 역류 식도염 환자의 식도 상피는 세포 사이 간격이 확장되어 있으며, 이는 프로톤 펌프 억제제 치료 후 호전된다고 한다. 이번 연구의 목적은 우리나라 역류 식도염 환자에서 식도 상피 세포 사이 간격이 확장되어 있는지 여부와 프로톤 펌프 억제제 치료 후 세포 사이 간격이 호전되는지 알아보았다. 대상 및 방법: 역류 식도염 증상이 있으며 상부위장관내시경 검사에서 점막 손상이 있는 역류 식도염 환자 10명과 위식도역류의 증상이 없고, 상부위장관내시경 검사에서 점막 손상이 없으며 24시간 보행 식도 산도 검사에서 음성인 정상인 10명을 대상으로 하였다. 모든 대상자에서 상부위장관내시경 검사를 시행하였으며, 위식도 경계부 5㎝ 상방에서 4군데 조직을 생검하여 전자 현미경으로 세포 사이 간격을 측정하였다. 모든 식도 조직의 전자 현미경 소견에서 100 번씩 세포 사이 간격을 측정하였다. 역류 식도염 환자는 8주간 esomeprazole로 치료한 후 내시경 검사를 하고 식도 상피 조직을 생검하여 세포 사이 간격을 다시 측정하였다. 결과: 역류 식도염 환자의 세포 사이 간격(평균 1.49±0.39 ㎛)은 대조군의 식도 상피 세포 사이 간격(평균 0.49±0.10 ㎛)보다 통계적으로 유의하게 확장되었다(p<0.01). 역류 식도염 환자에서 esomeprazole로 치료 후 세포 사이 간격(평균 0.56±0.19 ㎛)은 호전되었다(p<0.01). 결론: 우리나라 역류 식도염 환자의 식도 상피 세포 사이 간격은 정상인에 비해 확장된 소견을 보이며, 프로톤 펌프 억제제 치료 후 호전되었다. Background/Aims: It has been demonstrated that dilated intercellular spaces of esophageal epithelium are a marker of tissue injury in Western gastroesophageal reflux disease (GERD); which heals after proton pump inhibitor (PPI) treatment. The aim of this study was to determine whether dilated intercellular spaces are also a feature of acid damage in Korean GERD patients and are also healed after PPI treatment. Methods: Ten GERD patients with heartburn and esophageal mucosal breaks on endoscopy, and 10 controls with no symptoms, normal mucosa on endoscopy and negative 24-hour pH monitoring were enrolled. During upper gastrointestinal endoscopy, four biopsies from normal mucosa were taken within the lower 5 ㎝ of the esophagus for transmission electron microscopy (TEM) analysis. One hundred computer measurements were taken on TEM photomicrographs of the specimens in each patient. After eight weeks of esomeprazole 40 ㎎/day, patients with erosive esophagitis had another endoscopy with biopsies and the intercellular spaces were measured again. Results: The mean intercellular space diameter, in the erosive esophagitis patients, was greater than in controls (1.49±0.10 ㎛ vs 0.49±0.10 ㎛, p<0.01). The mean intercellular space diameter, in erosive esophagitis patients, improved after PPI treatment. Conclusions: Korean erosive esophagitis patients have dilated intercellular spaces of esophageal epithelium and dilated intercellular spaces can be reversed after esomeprazole treatment. (Kor J Neurogastroenterol Motil 2006;12:19-24)